Flow-cytometric evaluation of lymphocyte subpopulations in synchronously developing Schistosoma mansoni egg and Sephadex bead pulmonary granulomas. - Remick, D. G. (1988)
Synchronous models of T-cell-mediated and foreign body granulomas were induced in mice by intravenous embolization of Schistosoma mansoni eggs and Sephadex beads, respectively. The authors then performed flow-cytometric analysis of lymphocytes from dispersed granulomas, spleens, and peripheral blood at 4, 8, 16, and 32 days corresponding to the induction, growth, and maintenance, and resolution of these lesions. Lymphocytes were identified on the basis of light scatter characteristics, and the nature of the cells was confirmed by cell sorting and electron-microscopic examination. Lymphocyte subpopulations were characterized with antibodies to lymphocyte surface markers, specifically Ig, Thy 1.2, Lyt 1, Lyt 2, and L3T4. Natural killer cells were identified with anti-asialo GM1. Egg-induced granulomas had more lymphocytes of all phenotypes at all time points. Surprisingly, there was a significant number of cells staining positive for asialo GM1. On Day 16 after embolization there was a greater percentage of helper T cells, as defined by positive staining with L3T4, in the egg model, compared with the bead model. There was no obvious shift of lymphocytes from either the blood or spleen into the granuloma. These data confirm the importance of T cells in the direct participation of granulomatous inflammation, and the large numbers of asialo GM1-positive cells suggest a role for natural killer cells.